Small intestine diverticulum complicated by diverticulitis and enterolithiasis: Case report (Research, Society and Development, 2023)
Diverticula of the small intestine are a rare condition, often asymptomatic, but can present complications such as diverticulitis, bleeding and formation of enteroliths, which end up becoming a diagnostic challenge. With non-specific symptoms, they often require imaging tests, with computed tomography being the one that provides the greatest help for diagnosis. Although initially conservative management is possible in cases of obstruction secondary to enteroliths, the best alternative is surgical treatment for most complications. As it presents a mortality rate of up to 40% in cases of perforation, it is a differential diagnosis to be taken into account in the case of an acute abdomen, especially in the elderly population. This work aims to present a case of small diverticula complicated with diverticulitis and intestinal obstruction due to enterolith formation, as well as the images that helped with the diagnostic definition and the surgical treatment adopted that was successful in resolving the condition.